Recent progress and challenges of organometal halide perovskite solar cells. (28th January 2016) - Yang, Liyan; Barrows, Alexander T; Lidzey, David G; Wang, Tao
Abstract: We review recent progress in the development of organometal halide perovskite solar cells. We discuss different compounds used to construct perovskite photoactive layers, as well as the optoelectronic properties of this system. The factors that affect the morphology of the perovskite active layer are explored, e.g. material composition, film deposition methods, casting solvent and various post-treatments. Different strategies are reviewed that have recently emerged to prepare high performing perovskite films, creating polycrystalline films having either large or small grain size. Devices that are constructed using meso-superstructured and planar architectures are summarized and the impact of the fabrication process on operational efficiency is discussed. Finally, important research challenges (hysteresis, thermal and moisture instability, mechanical flexibility, as well as the development of lead-free materials) in the development of perovskite solar cells are outlined and their potential solutions are discussed.